PENERAPAN PENDIDIKAN NILAI PADA PELAJARAN PAI DI SMKN 1 PALABUHANRATU - Solahudin; Buchori, Imam; Faqih, Usman (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2025)
This research aims to determine the application of values ​​education in Islamic Religious Education (PAI) learning at SMKN 1 Palabuhanratu. Values ​​education has an important role in shaping the character of students so that they have good, responsible and religious personalities. The research method used is a qualitative approach with data collection techniques through observation, interviews and documentation studies. Research subjects included PAI teachers, students, and related school officials. The results of the research show that the application of values ​​education in PAI learning at SMKN 1 Palabuhanratu has been implemented through the integration of moral and religious values ​​into teaching materials and learning activities in the classroom and outside the classroom. Teachers act as role models and facilitators in instilling these values. Obstacles faced include limited learning time, lack of awareness among some students, and an external environment that is less supportive. Overall, the application of values ​​education in PAI learning at SMKN 1 Palabuhanratu has had a positive impact on the development of students' character. The recommendation from this research is the need to strengthen collaboration between schools, teachers and parents to increase the effectiveness of values ​​education in PAI learning.